2019
DOI: 10.6023/cjoc201809009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Insecticidal Activity of Novel Piperidine Thiazole Compounds

Abstract: 摘要 为了探寻新型的生物活性化合物, 设计并合成了 12 个未见文献报道的新型哌啶噻唑类衍生物. 生物活性测试研 究发现, 在 500 μg/mL 浓度下, 目标化合物对粘虫表现出良好的抑制活性, 而且在 100 μg/mL 下, (4-( 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…Other compounds exhibited poor fungicidal activities, which demonstrated that the thiazole ring is critical for the activity of oxathiapiprolin. Subsequently, when the terminal group was replaced and the remaining thiazole and piperidine rings in the oxathiapiprolin molecule unchanged (e.g., compounds 6 , 7 , 8 , and 9 ), their fungicidal activities have not been significantly improved, instead of certain insecticidal activities ( Zhu et al, 2016 ; Ding et al, 2019a ; Ding et al, 2019c ; Ding et al, 2020 ). However, Choi et al (2015) reported a novel compound 10 with high fungicidal and insecticidal activities through the modification of the thiazole ring in 2015, with the EC 50 value of 0.98 μM against P. capsici and the LC 50 value of 0.513 μM against Cx.…”
Section: Structural Modification Of Commercial Oxathiapiprolinmentioning
confidence: 99%
“…Other compounds exhibited poor fungicidal activities, which demonstrated that the thiazole ring is critical for the activity of oxathiapiprolin. Subsequently, when the terminal group was replaced and the remaining thiazole and piperidine rings in the oxathiapiprolin molecule unchanged (e.g., compounds 6 , 7 , 8 , and 9 ), their fungicidal activities have not been significantly improved, instead of certain insecticidal activities ( Zhu et al, 2016 ; Ding et al, 2019a ; Ding et al, 2019c ; Ding et al, 2020 ). However, Choi et al (2015) reported a novel compound 10 with high fungicidal and insecticidal activities through the modification of the thiazole ring in 2015, with the EC 50 value of 0.98 μM against P. capsici and the LC 50 value of 0.513 μM against Cx.…”
Section: Structural Modification Of Commercial Oxathiapiprolinmentioning
confidence: 99%
“…朱砂叶螨和苜蓿蚜采用喷雾法 [34] : 分别将 接有朱砂叶螨、苜蓿蚜的蚕豆叶片于 Potter 喷雾塔下进 行喷雾处理, 然后将苜蓿蚜放置在 20 ℃的观察室内进 行培养, 朱砂叶螨放置在 25 ℃的观察室内进行培养, 48 h 后观察实验的结果, 检查死活虫的数目, 进行数据 统计. 东方粘虫采用浸叶法 [35] : 将玉米叶放置于配好的 药液中充分浸润, 自然阴干后, 再放于垫有滤纸的培养 皿中, 接东方粘虫 3 龄中期幼虫 10 头/皿, 放在 25 ℃的 观察室内进行培养, 48 h 后观察实验的结果, 检查死活 虫的数目, 进行数据统计. 辅助材料(Supporting Information) 目标化合物 10a~ 10t 的核磁共振氢谱和碳谱图谱.…”
Section: 化合物 1~3 和 7~9 的合成unclassified
“…通过浸叶法 [21] 对粘虫(Oriental armyworm)进行了生 物活性评价, 另外通过喷雾法 [22] 2 Insecticidal activities of the target compounds 9a~9t (mortality/%) Compd.…”
Section: 生物活性mentioning
confidence: 99%